SILVER COLLAR IN HEALTH - Nilgün Bozbuğa; Eda Yılmaz Alarçin (Sabiad)
Due to the change in demographic, socio-cultural and economic structure in societies, the rapid development of technology and the differentiation of working culture, the structure of the workforce is also changing, and new concepts are emerging. In this conceptual study, it is suggested that the concept of “silver collars”, a phrase which has not been included in human resources terminology and literature before, could be used in the definition of health workers (excluding physicians), who provide services in the healthcare sector. Our pioneering essay discusses which nurses and allied health workers will be covered within the definition of silver collars with their professional and institutional commitment as career fields, keeping the organizational culture alive, maintaining the organizational climate, problem solving, and long-term social communication.